TINDAK PIDANA TERKAIT KEKERASAN SEKSUAL TERHADAP ANAK DALAM PERSPEKTIF PERLINDUNGAN ANAK DI BAWAH UMUR 5 TAHUN - Dedy Setiawan (Pascasarjana Ilmu Hukum, Universitas Widyagama Malang, 2020)
In this study shows that the legal protection of child victims of sexual crime according to positive law is to be based on Pancasila. Therefore, the protection of the law will give birth to the recognition and protection of human rights in its form as individual beings and social beings. Law enforcement against children who are victims of sexual crimes according to positive law must also be based on Pancasila in providing legal protection to its citizens, particularly law enforcement against children who are victims of sexual violence. Principles of protection for children in formal law, children receive preventive protection from the state and society, but the principles of child protection have not been implemented properly, in fact there are still many children who have not been protected from various forms of violence and exploitation and are still living neglected and do not get a chance to get a proper education, moreover adequate obstacles in implementing Law Number 35 of 2014 are positive laws in Indonesia. In an effort to protect children, various International Conventions and rules have been adopted but their implementation has not been maximized.